Cloning and sequencing of VP19-encoding gene of white spot syndrome virus from Situbondo’s isolate - Alim, Sahrul; Wahjuningrum, Dinamella; Ali, Muhamad (Jurnal Akuakultur Indonesia, 2011)
ABSTRACTWhite spot syndrome virus (WSSV) is the most dangerous shrimp pathogen and give a very bad impact to the shrimp industry in many countries, including Indonesia. Furthermore, the vaccine usage is less effective since the local WSSV suspected to have some mutation and have differences in sequence from the one that used for recombinant vaccine production so far. Therefore, it is necessary to produce recombinant vaccine for immunization of local shrimp according to WSSV isolates from Indonesia. Viral protein 19 (VP19) is an important WSSV envelope proteins because of its involvement in the systemic infection of shrimp, so it can be developed as a recombinant vaccine. The objectives of this study are to obtain VP19-encoding gene of WSSV from Situbondo, Indonesia. This research conducted through several stages, DNA genome isolation of Penaeus monodon infected with WSSV, amplification of VP19-encoding gene, isolation of VP19-encoding gene, ligation of VP19-encoding gene into pGEM-T Easy vector, transformation to Escherichia coli, recombinant vector screening, vector isolation using mini preparation technique, vector verification, and sequencing. The result of cloning shows that the size of VP19-encoding gene from Situbondo isolates is similar to VP19-encoding gene from the abroad one, which is 366 bp. However, the sequence result shows that there are some differences on bases and amino acid. However, the result of sequencing shows there are difference of five base and three amino acid arranged VP19 sequence the Situbondo isolate with isolate from several countries. The similiarity of the Situbondo isolate sequence with the other isolate (from Indonesian and other countries) was only 98%. This difference indicates the importance of making a vaccine from a local WSSV genes especially Situbondo isolate.Keywords: white spot syndrome virus, VP19, Penaeus monodonABSTRAKWhite spot syndrome virus (WSSV) merupakan patogen yang paling serius menyerang udang windu dan telah menghancurkan industri udang windu di berbagai negara, termasuk di Indonesia. Penggunaan vaksin WSSV yang didesain berdasarkan isolat WSSV luar negeri kurang efektif karena diduga WSSV yang menyerang udang Indonesia telah mengalami mutasi dan memiliki perbedaan sekuen. Untuk itu, penggunaan isolat WSSV asal Indonesia, khususnya Situbondo sebagai cetakan dalam memproduksi vaksin rekombinan untuk imunisasi udang di Indonesia sangat perlu dilakukan. Viral protein-19 (VP19) merupakan protein pembungkus WSSV yang penting karena keterlibatannya dalam infeksi sistemik pada udang, sehingga dapat dikembangkan sebagai vaksin rekombinan. Tujuan penelitian ini adalah untuk mendapatkan gen penyandi protein permukaan VP19 virus WSSV isolat Situbondo. Tahapan penelitian yang dilakukan pada penelitian ini adalah isolasi DNA genom udang windu yang terinfeksi WSSV, amplifikasi gen penyandi protein VP19, isolasi gen penyandi protein VP19, ligasi gen penyandi protein VP19 ke dalam plasmid pGEM-T Easy, transformasi plasmid, skrining plasmid rekombinan, isolasi plasmid dengan teknik mini preparation, verifikasi plasmid dan pengurutan. Hasil pengklonan menunjukkan bahwa ukuran gen penyandi protein VP19 isolat Situbondo sama dengan ukuran gen penyandi protein VP19 isolat asing yaitu 366 pb. Namun hasil pengurutan menunjukkan adanya perbedaan lima basa dan tiga asam amino penyusun sekuen VP19 isolat Situbondo dengan isolat dari beberapa negara lain. Kemiripan sekuen isolat Situbondo dengan isolat lain (dari Indonesia sendiri maupun dari negara-negara lain) hanya sebesar 98%. Adanya perbedaan ini mengindikasikan pentingnya pembuatan vaksin dari gen WSSV lokal khususnya isolat Situbondo.Kata kunci: white spot syndrome virus, VP19, Penaeus monodon